2021
DOI: 10.1038/s41598-021-94025-7
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic factors and the risk of Dupuytren’s disease: data from 30,000 individuals followed for over 20 years

Abstract: Dupuytren’s disease (DD) is a fibroproliferative disorder affecting the palmar fascia of the hand. Risk factors include diabetes mellitus (DM), whereas a high body mass index (BMI) is associated with a lower prevalence of DD. The aim of this study was to further elucidate risk and protective factors for the development of DD using longitudinal population-based data from the Malmö Diet and Cancer Study (MDCS). During 1991–1996, the inhabitants aged 46–73 years in the city of Malmö, Sweden were invited to partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
0
10
0
2
Order By: Relevance
“…At present, gender may also be one of the key factors affecting the occurrence of DC. For example, Rydberg et al [ 21 ] found a strong correlation between apolipoprotein levels and the occurrence of DC in patients of different genders. Another study found that androgens can act on the palmar fascia and the expression level of androgen receptors in patients with DC was significantly higher than that in normal palms, suggesting that androgen response status is associated with a higher incidence of DC in male patients [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, gender may also be one of the key factors affecting the occurrence of DC. For example, Rydberg et al [ 21 ] found a strong correlation between apolipoprotein levels and the occurrence of DC in patients of different genders. Another study found that androgens can act on the palmar fascia and the expression level of androgen receptors in patients with DC was significantly higher than that in normal palms, suggesting that androgen response status is associated with a higher incidence of DC in male patients [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, also several non-structural ECM proteins such as mimecan, periostin, decorin and TGFBI were upregulated in DC associated sweat glands. Mimecan, periostin, decorin and TGFBI are proteins that have been shown to interact with fibrillar collagens, growth factors and growth factor receptors and thus influence ECM assembly, cellular growth, and migration [ 1 , 2 , 3 ]. TGFBI has been shown to be induced by TGF-β [ 34 ] and can affect heart and renal fibrosis [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence rates of this disease depend on the population group analyzed and are significantly higher in middle-aged or older men of Northern European descent [ 2 ]. In addition, metabolic factors such as diabetes mellitus and excessive alcohol consumption constitute the main risk factors for development of DC [ 3 ]. Other risk factors include smoking, increasing age, male gender, epilepsy, and genetic predisposition [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The disease is one of the most common hereditary disorders of the connective tissue, and has strong associations with genetic profiles and family history [3]. In previous studies, male gender, diabetes mellitus, excess alcohol consumption and smoking were identified as major risk factors for its development [4,5]. The current worldwide prevalence of DC is estimated to be around 8.2% [6], a rate which varies greatly with geographic location.…”
Section: Introductionmentioning
confidence: 99%